2014
DOI: 10.4236/aim.2014.44024
|View full text |Cite
|
Sign up to set email alerts
|

Thiol-Mediated Reduction of <i>Staphylococcus aureus</i> Tellurite Resistance

Abstract: The goal of this work was to enhance tellurite toxicity against Gram positive bacteria, especially Staphyloccocus aureus. Using a combination of assays (growth inhibition zones, growth curves, and minimal inhibitory concentrations), tellurite toxicity against this bacterium was tested in the presence of various SH-and OH-containing compounds. Results showed that the noxiousness of tellurite was strongly enhanced in the presence of 2-mercaptoethanol or dithiothreitol. The potentiating effect was observed in S. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…The significant increase of ROS detected in E. coli cells exposed to tellurium NSs is also a usual response to tellurite exposure. As previously reported, S. aureus is much more resistant to tellurite than E. coli and generates smaller amounts of ROS in the presence of tellurite (23). The same trend is observed in Fig.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The significant increase of ROS detected in E. coli cells exposed to tellurium NSs is also a usual response to tellurite exposure. As previously reported, S. aureus is much more resistant to tellurite than E. coli and generates smaller amounts of ROS in the presence of tellurite (23). The same trend is observed in Fig.…”
Section: Discussionsupporting
confidence: 76%
“…As shown in Fig. S3 in the supplemental material, 2-ME greatly enhanced the antibacterial effect of the tellurium NSs, a phenomenon that was previously reported when both tellurite and 2-ME were simultaneously administered to S. aureus (23), supporting the putative tellurite release from the Te-containing nanostructures.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…This suggestion was confirmed when tellurium nano-rods were observed inside E. coli after being exposed to TeNPs. Alternatively, it has been reported by Pugin et al [ 34 ] that S. aureus exhibits much more resistance to tellurite and generates lower amounts of ROS which explains the resistance of S. aureus to TeNPs in the present study.…”
Section: Discussionmentioning
confidence: 40%
“…Although it may be surprising to obtain a resistant Staph aureus and sensitive MRSA, S. aureus resistance of methicillin has a different mechanism from that of ROS [ 39 ] and therefore the resistance of S. aureus to methicillin does not influence or interfere with its sensitivity to TeNPs. Furthermore, Pugin et al [ 34 ] showed no growth inhibition of S. aureus ATCC 6538 in presence of tellurium nano-particles.…”
Section: Discussionmentioning
confidence: 99%